2019
DOI: 10.3390/w11040749
|View full text |Cite
|
Sign up to set email alerts
|

Improved Approach for the Investigation of Submarine Groundwater Discharge by Means of Radon Mapping and Radon Mass Balancing

Abstract: The paper presents an improved approach for investigating submarine groundwater discharge (SGD) based on radon mapping and radon mass balancing in the coastal sea. While the use of radon as an environmental tracer in SGD studies is well-established, we identified based on our longstanding experience six methodical shortcomings of the conventional approach and suggest corresponding developments. The shortcomings include: (1 and 2) inadequate consideration of both detection equipment response delay and influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…For example, beyond the embayment scale, ocean-basin scale SGD estimates were recently performed using inventories of the relatively long-lived 228 Ra (Kwon et al, 2014). Uncertainties are often high for both radon and radium mass balance estimates, largely but not exclusively, because of the difficulty in constraining a value for the groundwater "endmember" (the concentration of the tracer in the discharging groundwater; Burnett et al, 2007;Schubert et al, 2019).…”
Section: Geochemical Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, beyond the embayment scale, ocean-basin scale SGD estimates were recently performed using inventories of the relatively long-lived 228 Ra (Kwon et al, 2014). Uncertainties are often high for both radon and radium mass balance estimates, largely but not exclusively, because of the difficulty in constraining a value for the groundwater "endmember" (the concentration of the tracer in the discharging groundwater; Burnett et al, 2007;Schubert et al, 2019).…”
Section: Geochemical Methodologymentioning
confidence: 99%
“…The latter issue was also tackled by Petermann and Schubert (2015), who introduced a methodology to correct radon data collected using an air-water exchanger (RAD-Aqua, Durridge) connected to a RAD-7 radon detector for its response delay when moving between high and low radon activity water masses. Schubert et al (2019) recently suggested additional improvements in the application of radon mass balance approaches that should improve corrections for radon losses from mixing and atmospheric evasion. Since the "early days" of SGD studies, there has been a natural progression in improving radon measurement methodologies from labor-intensive grab samples collected in the field and analyzed in the lab or on ships (Mathieu et al, 1988), to the use of automated systems such as the RAD-AQUA (Burnett et al, 2001), to completely automated detection systems that can work unattended for months to years.…”
Section: Geochemical Methodologymentioning
confidence: 99%
“…Applicable tracers include the stable isotopes of water (e.g., [7][8][9][10][11][12][13]) as well as naturally occurring radioisotopes. Examples for the latter are 35-sulphur, 3-hydrogen (tritium), 222-radon, and the radium 224/223 ratio (e.g., [14][15][16][17][18][19]). Major ions and trace elements are also frequently applied as tracers (e.g., [20][21][22]).…”
Section: Introductionmentioning
confidence: 99%
“…Representative average wind speeds (scaled to 10 m above the surface) are estimated in four different ways and then subsequently used to derive gas transfer velocities from the wind-k equation of MacIntyre et al (1995) (2) average wind speed during the 24 h before the end of the sampling (u = 2.0 m s −1 ); (3) average wind speed during the 48 h before the end of the sampling (u = 3.5 m s −1 ); (4) weighting the influence of degassing on radon concentration depending on their proximity to the sampling time (i.e., events closer to the sampling campaign are more influential). A weighting factor for the importance of degassing events depending on its proximity to the sampling campaign (w t ) is adapted from (Schubert et al 2019) based on the radon decay constant (λ) and the gas transfer velocity (k) as primary controls on radon inventories for La Palme Lagoon:…”
Section: Gas Transfer Velocities For Radon Kmentioning
confidence: 99%